1994
DOI: 10.1111/j.1365-313x.1994.00331.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of cytosolic free calcium in the reorientation of pollen tube growth

Abstract: Summary Growing pollen tubes of Agapanthus umbellatus exhibited a tip‐to‐base gradient in cytosolic free calcium ([Ca2+]c). Although this gradient is believed to be involved in pollen tube growth, its role in specifying reorientation is unknown. The direction of pollen tube growth could be modified by iontophoretic micro‐injection, electrical fields (EFs) or photolysis of caged Ca2+. Iontophoretic injection resulted in a temporary cessation of growth, an increase in [Ca2+]c and, upon recovery, reoriented growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
142
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 174 publications
(150 citation statements)
references
References 19 publications
8
142
0
Order By: Relevance
“…Very low concentrations of the channel blockers, La 3+ or Gd 3+ , slightly diminish growth rates but completely block reorientation of the pollen tube in response to an applied electrical ¢eld. Several types of Ca 2+ channel may thus be present (Malho¨et al 1994). This initiation site is an important model for other plant cells.…”
Section: The Calcium Wavementioning
confidence: 99%
See 3 more Smart Citations
“…Very low concentrations of the channel blockers, La 3+ or Gd 3+ , slightly diminish growth rates but completely block reorientation of the pollen tube in response to an applied electrical ¢eld. Several types of Ca 2+ channel may thus be present (Malho¨et al 1994). This initiation site is an important model for other plant cells.…”
Section: The Calcium Wavementioning
confidence: 99%
“…Photolysis of loaded caged (1,4,5) InsP 3 in the presence of heparin (to inhibit binding to the (1,4,5) InsP 3 channel) induced only truncated waves (Franklin-Tong et al 1996). A decline in membrane potential induced by brief iontophoresis opens voltage-gated plasma membrane Ca 2+ channels and elevates [Ca 2+ ] c through extensive regions of the pollen tube (Malho¨et al 1994. Pollen tubes also possess a Ca 2+ -activated phospholipase C capable of generating (1,4,5) InsP 3 (Franklin-Tong et al 1996).…”
Section: (F) Propagation Of Ca 2+ Waves In the Cytoplasmmentioning
confidence: 99%
See 2 more Smart Citations
“…This essential ion (Brewbaker and Kwack, 1963) forms a steep tipfocused gradient at the extreme apex of the tube (Rathore et al, 1991;Miller et al, 1992;Malhó et al, 1994;Pierson et al, 1994;Roy et al, 1999) where it may stimulate exocytosis (Battey et al, 1999;Roy et al, 1999). Further studies have revealed that the Ca 2+ gradient oscillates in magnitude with the same period as growth rate; however, it follows the increase in growth rate by 10 to 408 (Messerli et al, 2000;Cá rdenas et al, 2008).…”
Section: Introductionmentioning
confidence: 99%